2015
DOI: 10.1371/journal.pone.0134062
|View full text |Cite
|
Sign up to set email alerts
|

Robotic versus Laparoscopic Approach in Colonic Resections for Cancer and Benign Diseases: Systematic Review and Meta-Analysis

Abstract: ObjectivesThe aim of this systematic review and meta-analysis is to compare robotic colectomy (RC) with laparoscopic colectomy (LC) in terms of intraoperative and postoperative outcomes.Materials and MethodsA systematic literature search was performed to retrieve comparative studies of robotic and laparoscopic colectomy. The databases searched were PubMed, Embase and the Cochrane Central Register of Controlled Trials from January 2000 to October 2014. The Odds ratio, Risk difference and Mean difference were us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
62
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(70 citation statements)
references
References 56 publications
(77 reference statements)
7
62
1
Order By: Relevance
“…Similar conclusions have been drawn from an extensive meta-analysis in 2015 comparing robotic versus laparoscopic colorectal resections, which also pointed out a lower incidence of peri-operative complications and surgical site infections [13].…”
Section: Colorectal Surgery: the Subspecialty That Paved The Waysupporting
confidence: 76%
“…Similar conclusions have been drawn from an extensive meta-analysis in 2015 comparing robotic versus laparoscopic colorectal resections, which also pointed out a lower incidence of peri-operative complications and surgical site infections [13].…”
Section: Colorectal Surgery: the Subspecialty That Paved The Waysupporting
confidence: 76%
“…The incidence of ileus was similar between RRH and LRH; however, in four studies passing of first flatus was reported to be significantly earlier in RRH (2.0–2.7 days vs 2.5–4.0 days). This finding has been previously highlighted in studies with a meta‐analysis analysing the robotic vs laparoscopic approach in colonic resection for both cancer and benign diseases . Trastulli et al .…”
Section: Discussionmentioning
confidence: 56%
“…[10][11][12][13][14][15][16][17] In general, authors have found robotic surgery to be feasible and safe, referring to it as submit your manuscript | www.dovepress.com…”
Section: Introductionmentioning
confidence: 99%
“…A consistent conclusion in the majority of papers is that robotic colorectal surgery tends to be associated with a higher cost and a longer operative time. [13][14][15][16][17] However, the quality of these studies and consequently the conclusions drawn should be subjected to greater scrutiny. Most of these publications have been either case series or retrospective comparative studies.…”
mentioning
confidence: 99%